A novel cartilage-targeting MOF-HMME-RGD sonosensitizer combined with sonodynamic therapy to enhance chondrogenesis and cartilage regeneration - Luo, Shanchao; Shang, Yifeng; Qin, Zainen; Zhou, Bo; Lu, Chun; Qu, Yangyang; Zhao, Jinmin; Liang, Ruiming; Zheng, Li; Luo, Shixing (Frontiers in Bioengineering and Biotechnology, 2024)
Articular cartilage regeneration is still a difficult task due to the cartilage's weak capacity for self-healing and the effectiveness of the available therapies. The engineering of cartilage tissue has seen widespread use of stem cell-based therapies.However, efficient orientation of line-specific bone marrow mesenchymal stem cells (BMSCs) to chondrogenesis and maintenance of chondrogenic differentiation challenged stem cell-based therapy. Herein, we developed a Fe-based metal-organic framework (MOF) loaded with hematoporphyrin monomethyl ether (HMME) and cartilage-targeting arginine-aspartate-glycine (RGD) peptide to form MOF-HMME-RGD sonosensitizer to regulate BMSCs chondrogenic differentiation for cartilage regeneration via the modulation of reactive oxygen species (ROS). By using sonodynamic therapy (SDT), the MOF-HMME-RGD demonstrated favorable biocompatibility, could generate a modest amount of ROS, and enhanced BMSC chondrogenic differentiation through increased accumulation of glycosaminoglycan, an ECM component specific to cartilage, and upregulated expression of key chondrogenic genes (ACAN, SOX9, and Col2a1). Further, transplanted BMSCs loading MOF-HMME-RGD combined with SDT enhanced cartilage regeneration for cartilage defect repair after 8 weeks into treatment. This synergistic strategy based on MOF nanoparticles provides an instructive approach to developing alternative sonosensitizers for cartilage regeneration combined with SDT.